Student at Risk PBL Case - Rose-Claire St. Hilaire; Kalman Winston; Jina Harris-Alleyne; Diana Callender; Valarie Thomas; Sean Gnecco; Maureen Hall; Greg Ogrinc; Richard Frankel (Association of American Medical Colleges, 2013)
Abstract This resource is a progressive-disclosure problem-based learning case designed to sensitize students on behaviors that can influence their academic performance and highlight resources that are available to help them achieve their academic goals. The case involves a fictional student named Lenard Dickson. The case allows students to explore behaviors that may influence their learning and academic performance. The case is designed to run in groups of eight to nine students. On the first day, students are introduced to the problem-based learning process method. Students are asked to research the learning issues outside the session and return to the next session prepared to present their findings to fellow group members. Among the issues raised in this case are issues of study habits, sleep, learning, and the effects of drugs and alcohol on learning. The case is designed to show students the learning and support systems that are available on campus. They are expected to be able to identify the behavior of Lenard in themselves and other students. As this form of problem-based learning is more directive than traditional ones, the facilitator notes contain prompts which helps them guide students to particular learning goals. In addition, since no one person is an expert on all the issues raised, we provide facilitator notes with background information. This case was developed in 2009 and was used in the problem-based learning program for first-semester students. Data from research conducted on this case show that 85% of students were made more aware of available student support services. In addition, 57% of students surveyed said that behavior changes were implemented after working through this case, mainly in terms of sleep habits, study habits, and stress management.